Leksell radiosurgery - Leksell, Dan (Progress in neurological surgery / series editor L. Dade Lunsford, 2019)
Since its introduction 52 years ago, Leksell radiosurgery has become a widely applied technique for the management of a diverse group of vascular, neoplastic, and functional disorders. This publication presents an update on state-of-the-art radiosurgery technology, including outcomes, by the pioneers in the field. Experts have contributed chapters on various topics. They provide a history of the development of Leksell Gamma Knife and its evolution from frame-based to the inclusion of mask-based radiosurgery in the latest Gamma Knife model. For beginners, there is valuable information related to imaging, quality assurance, patient care, anesthesia, and regulatory requirements. Advance users will appreciate the summary of the long-term outcome of important indications. Additional chapters on cavernous malformation, orbital, uveal, and ocular disorders clarify the role of radiosurgery. This book is a concise overview for physicians interested in radiosurgery. It will be of great value to neurosurgeons, radiation oncologists, and medical physicists concerned with learning about the indications of radiosurgery.